Evaluation of prescription pattern and patients’ opinion on healthcare practices in selected primary healthcare facilities in Ibadan, South-Western Nigeria (2015)
Background: Inappropriate prescribing negatively impacts on health and economy of individual and the society. Objectives: To evaluate the prescribing patterns and patients’ opinions on healthcare practices in selected primary healthcare centres (PHC) in Ibadan, South-Western Nigeria. Methods: A prospective cross-sectional study was carried out among patients and healthcare workers in selected PHCs using semi-structured questionnaires. Also, patients’ prescription records were reviewed using the WHO-prescribing indicators. Results: About one-half (210; 52.5%) were very satisfied with convenience of obtaining prescribed medicines in the PHCs, accessibility of PHC to abode (158;39.5%) and affordable medications (136;34.0%). Patients were dissatisfied with follow-up of care (191; 47.8%), courtesy of workers (184; 46.3%) and non-availability of medicines (138;34.5%). Number of drugs per encounter was 5.8±2.3 and % encounter with an antibiotic was >26.8% in each facility. Hematinics accounted for (814; 35.0%), analgesics (544; 23.4%), antimicrobials (303;13.0%) and antihypertensives (5; 0.2%). Conclusion: Primary healthcare attendees were satisfied with medication costs affordability and accessibility of PHC to abode but expressed dissatisfaction with follow-up of care and courtesy of workers. Also, inappropriate prescriptions characterized by polypharmacy and overuse of antibiotics were common underscoring the need for regular training of PHC workers on rational drug use and instituting appropriate measures for improvement